Peran Ganda Wanita Tani Dalam Usahatani Sayuran dan Peningkatan Pendapatan di Desa Nangamua Kecamatan Arut Utara Kabupaten Kotawaringin Barat - Novi Nurhayati (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2018)
Agriculture is the main source of livelihood for Indonesian people. Women or housewives in Nangamua Village are generally vegetable farmers. Women here play a dual role, women as housewives are also the backbone of the family. The purpose of this study was to determine the role of women and the outpouring of female labor devoted to vegetable farming, the contribution of vegetable farming income to family income and the relationship between the amount of labor spent by female farmers and the amount of family income. The method used is descriptive analysis, income analysis and correlation analysis. The results of this study were that female farmers had a role in vegetable farming, such as seeding, planting, maintaining, harvesting and post-harvest, outpouring of female farm laborers in vegetable farming was 42.49% of all vegetable farming activities, vegetable farming opinion contribution in income the family is 33.33% and the correlation of the outpouring of female labor with vegetable farming income has a positive correlation with a value of 0.70.